Oxygen stable isotopes variation in water precipitation in Poland – anthropological applications - Lisowska-Gaczorek, Aleksandra; Cienkosz-Stepańczak, Beata; Szostek, Krzysztof (Anthropological Review, 2017)
The main objective of oxygen isotope analysis is to determine the probable place of origin of an individual or the reconstruction of migration paths. The research are methodologically based on referencing oxygen isotope ratios of apatite phosphates (δ18Op) to the range of environmental background δ18O, most frequently determined on the basis of precipitation.The present work is a response to the need for providing background for oxygen isotope studies on skeletons excavated in Poland. Currently there no monitoring of the isotope composition of precipitation water in Poland is conducted. For this reason, based on the data generated in the Online Isotopes In Precipitation Calculator (OIPC), a database was developed, containing δ18O levels in precipitation for locations in which exploration work was carried out in the archaeological fields from Poland. In total, 279 locations were analysed. The result of the data analysis was a complete isotope composition map for Poland with four zones distinguished by δ18Ow values.The observable differences in oxygen isotope composition of precipitation in Poland are sufficient to trace migrations of individuals and populations, although accurate only at the level of macroregions.